Treatment of Nevus de Ota with 755 nm Alexandrite Q-Switched Laser: Tratamiento de Nevus de Ota con Láser Q-Switched Alexandrita de 755 nm - Negron Beuzeville, Julio Cesar (2019)
Introduction: Ota nevus is a benign dermal melanocytic hamartoma with a macular appearance, poorly defined and in a gray-black patch that generally affects the first and second branches of the trigeminal unilaterally. Objective: To evaluate the efficacy, safety and adverse events caused by the application of 755 nm Alexandrite laser for the treatment of Ota nevus. Methods: Case series of 10 phototype IV patients with unilateral Ota Nevus treated between January 2017 and December 2018, which were treated with this light energy and with defined parameters. Results: The mean age was 29 years. The patients who completed the treatment did not show repigmentation in the treated lesion and the satisfaction index was acceptable. It was observed that the average of sessions to obtain favorable results varied between 8 and 10 applications. Among the most important adverse effects, post-inflammatory hyperpigmentation and the removal of the superficial layer of the post laser skin stand out. All were controlled without leaving permanent residual lesions. Conclusion: The 755 nm Alexandrite Q-switched laser is an effective technology to achieve a high degree of depigmentation in the treatment of Ota nevus and can be considered as a first-line treatment for the management of this pathology.